Retrospektivna analiza podatkov o vsajenih spodbujevalnikih tipa VDD v KC Ljubljana - Lipar, Luka (Zdravniški vestnik, 2005)
Background. VDD pacing system offers physiologically beneficial atrio-ventricular (AV) synchronous pacing. The objective of our analysis was to evaluate changes of parameters that determine hemodynamic efficiency of pacing over time. Methods. 358 patients who had implanted VDD pacemaker between May 1994 and September 2001 were retrospectively enrolled into our study. Data on P were amplitudes, AV synchrony, AF burden and pacing mode wereobtained from regular follow-up print outs. Results. P wave amplitudes have lowered over years. Fourth year after implantation amplitudes were 81% ofthose one year after implantation. AV synchrony did not change over years and was nearly constant at 80%. AF burden has increased in 5 years for 65% according to first year after implantation. AF burden was higher with patientsthat had their devices implanted more than 5 years ago compared to those that had devices implanted less than 5 years ago. The difference was statistically significant (p<0.05). VDD mode survival over 8 years was 88%. The most common indication for reprogramming was atrial fibrillation. Conclusions. We may assume that VDD pacing system is reliable yet hemodinamically less efficient. It remains to be unclear whether this has an impact on the incidence of AF, therefore further studies are required.
Keywords: Atrial Fibrillation; Cardiac Pacing, Artificial; Časovni faktorji; Methods; Preddvorna fibrilacija; Retrospective Studies; Retrospektivne študije; Srčno vzpodbujanje, umetno; Time Factors